2020
DOI: 10.1007/s10072-020-04598-w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum uric levels in migraine

Abstract: Objective In our study, the aim was to identify the serum uric acid levels, a marker of oxidative stress, according to migraine subtypes (aura/without aura and episodic/chronic migraine). Method The study included 300 migraine patients and 150 healthy controls for a total of 450 individuals. Migraine and subtypes were diagnosed according to International Classification of Headache Disorders-2013 criteria. Patients were evaluated during attendance at the neurology clinic. Results Our patient group was 77.0% fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…UA is the final product of purine metabolism ( 25 ) and can scavenge reactive oxygen species in the body ( 26 ). Yazar et al reported that UA levels were lower in patients with migraine ( 27 ), which was consistent with our findings. UA acts as an endogenous antioxidant that can reduce oxidative damage and inhibits inflammatory responses, which reduces the permeability of the blood-brain barrier (BBB) and exerts neuroprotective effects ( 28 ).…”
Section: Discussionsupporting
confidence: 93%
“…UA is the final product of purine metabolism ( 25 ) and can scavenge reactive oxygen species in the body ( 26 ). Yazar et al reported that UA levels were lower in patients with migraine ( 27 ), which was consistent with our findings. UA acts as an endogenous antioxidant that can reduce oxidative damage and inhibits inflammatory responses, which reduces the permeability of the blood-brain barrier (BBB) and exerts neuroprotective effects ( 28 ).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the contradiction of anti-oxidant effects and pro-oxidant effects might be due to the dose effect of serum urate (13). A previous study showed that a lower serum urate level was found in migraine, which was not influenced by the subtypes of migraine (14). However, another study found that serum urate in migraine might be more than control group, which had not shown the results of statistical hypothesis testing (15).…”
Section: Introductionmentioning
confidence: 96%
“…These values were well within the normal range (male 3.4-7 mg/dl, female 2.4-5.7 mg/dl); and there was also no statistically significant difference in uric acid levels in either gender. Many other studies have also reported non-significant difference in serum uric acid levels between migraine cases and healthy controls [13,16]. We could not find any study which had compared uric acid levels between male and female migraine patients.…”
Section: Discussionmentioning
confidence: 60%
“…Many others studies have also reported similar mean age of migraine patients [13,14]. Most of the studies have earlier proved that migraine is common in female patients [14,15].…”
Section: Discussionmentioning
confidence: 65%